An empirical investigation of cash waqf contribution in selected states in Malaysia: an extended theory of planned behaviour / Wan Musyirah Wan Ismail - Wan Ismail, Wan Musyirah (2023)
The lack of cash waqf collection in Malaysia is due to various factors such as lack of awareness, trust, and misperception of cash waqf. The data collected from Yayasan Waqf Malaysia shows that the contribution of cash waqf was only RM0.28 per employed Muslim for 2019. Hence, the motive to increase the collection of cash waqf should be an important agenda in improving the beneficiaries' socio economy and wellbeing. Thus, identifying the factors that influence Muslims to contribute cash waqf may help in achieving this goal. The Theory of Planned Behaviour (TPB) was used to identify the behaviour of Muslims in contributing cash waqf. Furthermore, the extended variables of technology acceptance and technology usage and moderator variable of perception on performance of cash waqf were used to extend the TPB to fill the literature and methodological gaps. These variables lead to the formation of the research framework and eight hypotheses to be investigated in the present study. This study is based on data obtained from a survey using structured questionnaire involving employed Muslims in Selangor, Kuala Lumpur and Johor which constitute the highest employed people with the highest income and payment salary, as well as the highest collection of cash waqf. Data collected from 316 respondents were analysed using PLSSEM. The results show that the attitude, subjective norms, and perceived behavior control as well as technology acceptance and technology usage were positively significant influence the intention to contribute cash waqf. The moderator variable significantly influences the relationship between subjective norms with behavior intention and perceived behaviour control with behaviour intention. However, the moderator variable was found to have an insignificant influence on relationship between attitude with intention to contribute cash waqf. Thus, this study emphasizes the role of technology that needs to be implemented in cash waqf collection to increase contributions among Muslims in Malaysia. The study suggests the researcher for further research using other variables as extended variables or employing another moderator variable, or the inclusion of a mediator variable. The study also suggests increasing the number of states in future inquiries.